Mechanistic Insights into the Inhibition of SARS-CoV-2 Main Protease by Clovamide and Its Derivatives: In Silico Studies - Naike Ye; Francesco Caruso; Miriam Rossi (Biophysica, 2021)
The novel coronavirus SARS-CoV-2 Main Protease (Mpro) is an internally encoded enzyme that hydrolyzes the translated polyproteins at designated sites. The protease directly mediates viral replication processes; hence, a promising target for drug design. Plant-based natural products, especially polyphenols and phenolic compounds, provide the scaffold for many effective antiviral medications, and have recently been shown to be able to inhibit Mpro of SARS-CoV-2. Specifically, polyphenolic compounds found in cacao and chocolate products have been shown by recent experimental studies to have strong inhibitory effects against Mpro activities. This work aims to uncover the inhibition processes of Mpro by a natural phenolic compound found in cacao and chocolate products, clovamide. Clovamide (caffeoyl-DOPA) is a naturally occurring caffeoyl conjugate that is found in the phenolic fraction of Theobroma Cacao L. and a potent radical-scavenging antioxidant as suggested by previous studies of our group. Here, we propose inhibitory mechanisms by which clovamide may act as a Mpro inhibitor as it becomes oxidized by scavenging reactive oxygen species (ROS) in the body, or becomes oxidized as a result of enzymatic browning. We use molecular docking, annealing-based molecular dynamics, and Density Functional Theory (DFT) calculations to study the interactions between clovamide with its derivatives and Mpro catalytic and allosteric sites. Our molecular modelling studies provide mechanistic insights of clovamide inhibition of Mpro, and indicate that clovamide may be a promising candidate as a drug lead molecule for COVID-19 treatments.